Experiences of returning to elite beach volleyball after shoulder injury - Bele, S.; Hafsteinsson Östenberg, A.; Sjöström, R.; Alricsson, M. (Journal of Exercise Rehabilitation, 2015)
The purpose of this study was to examine beach volleyball players` experience regarding shoulder injury and how it affects their return to play. To achieve the research aims a qualitative design with semi-structured interviews had been conducted, five elite beach volleyball players, four men and one woman aged 27-42 participated in the study. All participants had suffered a severe shoulder injury, with absence from training and competing for at least 28 days. The findings of this study indicate that it is the individual`s inner motivation, together with a clear goal and support from the community, family, teammate and coach that are the most important factors when going through rehabilitation and getting back to playing beach volleyball after a shoulder injury. All participants had been affected by their injury in some way; some of the participants had been affected in a positive way since they had become mentally stronger and had developed better volleyball technique after rehabilitation. The conclusions of this study indicate that there are three distinct factors that increase the chances of getting back to playing beach volleyball after shoulder injury; it is the players` self motivation, together with a clear goal and support from the community.